IMPLEMENTASI PROGRAM ADIWIYATA UNTUK MENGEMBANGKAN KARAKTER PEDULI LINGKUNGAN SISWA DI SDN CIBEUREUM KOTA TASIKMALAYA - Fitri Yanni; Syarip Hidayat (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article examines the implementation of the Adiwiyata program to develop students’ environmental care character at SDN Cibeureum, Tasikmalaya. The study used a qualitative case study with descriptive analysis. The subjects involved the principal, Adiwiyata program coordinator, teachers, and students. Data were collected through observation, interviews, and documentation and analyzed using Miles and Huberman’s stages of data collection, reduction, presentation, and conclusion. The results indicated that the Adiwiyata program effectively developed students’ environmental care character through organized activities, such as establishing a picket schedule, plant care activities including planting, fertilizing, and watering, and proper waste management by distinguishing organic, inorganic, and hazardous waste. This study provides insights into character development through environmental programs and can motivate other schools to implement the Adiwiyata program.